PENINGKATAN KETERAMPILAN MEMBACA TEKS BIOGRAFI MENGGUNAKAN MODEL COOPERATIVE TALKING STICK - Yulita, Desy; Salem, Laurensius; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is based on the low skills of students in reading. The low level of students 'skills in reading is caused by a lack of interest in students' learning in reading and lack of concentration in reading. This study focused on reading biographical material using the Cooperative Talking Stick model. The formulation of the problem in this study is how planning, implementation, and results of intensive reading learning using the Cooperative Talking Stick model. The purpose of this study is to describe the planning, implementation, and learning outcomes of reading biographical texts using the Cooperative Talking Stick model. The method used in this research is descriptive method. The forms of qualitative and quantitative research, and the design is Classroom Action Research (PTK). The instruments used were assignment of questions reading biographical texts, teacher assessment sheets, and observation sheets of students' attitudes and activities. Research data is processed qualitatively and quantitatively. This research was carried out 2 cycles 1 cycle 1 meeting. After getting action in the first cycle the percentage of completeness became 73.33%. An increase in cycle II was 92.59%. Thus, learning to read biographical texts using the Cooperative Talking Stick model in students of class X of Social Sciences 3 Tekarang State 1 High School has increased. Cooperative Talking Stick learning model is in accordance with the characteristics of high school students, therefore it is better to use Cooperative Talking Stick learning models for learning. Keywords: Reading Biographical Text, Cooperative Talking Stick